James Mellaart: A review of a recent book, some personal memories, and archaeological deception - Davey, Christopher J. (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
Alan C. Mellaart’s book about his father James Mellaart: The Journey to Çatalhöyük is reviewed. The memories of the author, who attended Mellaart’s lectures at the Institute of Archaeology, London, are recounted and discussed in relation to the Dorak affair. The paper also includes the perspective of G.R.H. (Mick) Wright, who excavated with Mellaart in the 1950s. The discussion reflects on the context and consequences of the controversies surrounding Mellaart.